Examining the role of green finance, trade-adjusted carbon emissions and major green economic variables for the BRICST economies - Karambir Singh Dhayal; Rijaa Zaka; Muhammad Kamran Khan; Arun Kumar Giri; Tiong Ying Ying (Discover Sustainability)
Abstract The BRICST (Brazil, Russia, India, China, South Africa and Turkey) region has experienced rapid economic growth in the last two decades, significantly contributing to the global GDP, population and carbon emissions. Because of their rapid industrial expansion, these economies face environmental challenges that necessitate a transition toward sustainable economic practices. The present study identifies the significant research gap by analyzing the BRICST region studies through thematic mapping. It investigates the impact of the various green economic variables, namely green finance, green trade, green environmental concerns, green energy, green growth and green patents towards trade-adjusted carbon emissions through the MMQR econometric technique. The study provides empirical evidence to support policy interventions to accelerate green growth and climate-resilient economic transitions. These findings offer valuable insights for policymakers, financial institutions and international organizations, emphasizing the need for integrated green strategies to achieve long-term environmental and economic sustainability. The study’s findings indicate that all these green economic parameters help to reduce emissions and thus contribute to the greening of the BRICST region.